2015
DOI: 10.1002/cne.23891
|View full text |Cite
|
Sign up to set email alerts
|

Marked differences in the number and type of synapses innervating the somata and primary dendrites of midbrain dopaminergic neurons, striatal cholinergic interneurons, and striatal spiny projection neurons in the rat

Abstract: Elucidating the link between cellular activity and goal-directed behavior requires a fuller understanding of the mechanisms underlying burst firing in midbrain dopaminergic neurons and those that suppress activity during aversive or non-rewarding events. We have characterized the afferent synaptic connections onto these neurons in the rat substantia nigra pars compacta (SNpc) and ventral tegmental area (VTA), and compared these findings with cholinergic interneurons and spiny projection neurons in the striatum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 68 publications
(112 reference statements)
2
9
0
Order By: Relevance
“…However, the punctate expression patterns and higher density of PSD95.FingR-labeled synapses than Gephyrin.FingR-labeled synapse suggest that the FingR vectors correctly identify excitatory and inhibitory synapses. Furthermore, the synaptic densities we report for excitatory synapses in adult-born granule cells and for inhibitory synapses in striatal cholinergic interneurons are in line with previous studies ( Sizemore et al., 2016 , 2010 ; Sultan et al., 2015 ; Toni et al., 2007 ; van Praag et al., 2002 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, the punctate expression patterns and higher density of PSD95.FingR-labeled synapses than Gephyrin.FingR-labeled synapse suggest that the FingR vectors correctly identify excitatory and inhibitory synapses. Furthermore, the synaptic densities we report for excitatory synapses in adult-born granule cells and for inhibitory synapses in striatal cholinergic interneurons are in line with previous studies ( Sizemore et al., 2016 , 2010 ; Sultan et al., 2015 ; Toni et al., 2007 ; van Praag et al., 2002 ).…”
Section: Discussionsupporting
confidence: 92%
“…Striatal cholinergic interneurons receive afferent input with a wide variety of neurotransmitters (Lim et al, 2014), including glutamatergic input from especially the intralaminar thalamic nuclei (Assous and Tepper, 2019), nigrostriatal dopaminergic input (Lim et al, 2014) and cholinergic input from other cholinergic interneurons. Although dopaminergic projections to MSNs are by far more abundant than those on cholinergic interneurons (Sizemore et al, 2016), the majority of these interneurons express inhibitory dopamine D2 receptors next to excitatory D5 receptors, and about 20% contain low levels of excitatory D1 receptors (Lim et al, 2014). Nigrostriatal projections largely enhance the activity of certain CSTC circuits by affecting specific MSNs and modify the activity of a group of MSNs by inhibiting the more widespread activity of cholinergic interneurons.…”
Section: The Mechanism Of Drug-induced Dystoniamentioning
confidence: 99%
“…Studies in different animal models have shown that the damage of dopaminergic neurons in the SNc is clear. This condition may be due to the following reasons: First, many synaptic connections exist in dopaminergic neurons in the SNc [45]. Thus, the frequency of neuron activity is high and accompanied by high metabolism.…”
Section: Neural Plasticitymentioning
confidence: 99%